Spekulationsfeber. Finansielle fiktioner i Émile Zolas "Penge" - Andersen, Michael Høxbro (Passage - Tidsskrift for litteratur og kritik, 2014)
Michael Høxbro Andersen: “Speculation Fever. Financial Fiction in Émile Zola’s Money” One of the many French novels from the latter half of the 19th century that describes the stock exchange is Émile Zola’s Money from 1899. This article focuses on the two stylistic devises that Zola uses to describe stock market speculation: long, elaborated descriptions and metaphors. The article suggests that these devices cannot simply be read as Zola’s inability to grasp the abstract reality of financial capitalism. Against such a classical Marxist reading, expressed in different ways by György Lukács and Theodor W. Adorno, the article argues that Zola’s metaphors express an insight into the cyclic and entropic history of financial capitalism.